2011
DOI: 10.1038/ng.783
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association identifies a susceptibility locus for coronary artery disease in the Chinese Han population

Abstract: Coronary artery disease (CAD) causes more than 700,000 deaths each year in China. Previous genome-wide association studies (GWAS) in populations of European ancestry identified several genetic loci for CAD, but no such study has yet been reported in the Chinese population. Here we report a three-stage GWAS in the Chinese Han population. We identified a new association between rs6903956 in a putative gene denoted as C6orf105 on chromosome 6p24.1 and CAD (P = 5.00 × 10⁻³, stage 2 validation; P = 3.00 × 10⁻³, P =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
194
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 236 publications
(204 citation statements)
references
References 27 publications
5
194
3
Order By: Relevance
“…In the first years of GWAS discoveries, identification of further loci came from individual genome‐wide association studies (Erdmann et al , 2009; Myocardial Infarction Genetics Consortium et al , 2009; Tregouet et al , 2009; IBC 50K CAD Consortium, 2011; Wang et al , 2011), whereas more recently the formation of large, international consortia has accumulated a sufficient statistical power for new discoveries. The joint forces of the CARDIoGRAM (Schunkert et al , 2011), C4D (Coronary Artery Disease C4D Genetics Consortium, 2011) and finally the CARDIoGRAMplusC4D (CARDIoGRAMplusC4D Consortium et al , 2013; Nikpay et al , 2015) consortium allowed the analysis of up to 180,000 individuals, about half of which had CAD.…”
Section: Genome‐wide Association Studies In Coronary Artery Disease Amentioning
confidence: 99%
“…In the first years of GWAS discoveries, identification of further loci came from individual genome‐wide association studies (Erdmann et al , 2009; Myocardial Infarction Genetics Consortium et al , 2009; Tregouet et al , 2009; IBC 50K CAD Consortium, 2011; Wang et al , 2011), whereas more recently the formation of large, international consortia has accumulated a sufficient statistical power for new discoveries. The joint forces of the CARDIoGRAM (Schunkert et al , 2011), C4D (Coronary Artery Disease C4D Genetics Consortium, 2011) and finally the CARDIoGRAMplusC4D (CARDIoGRAMplusC4D Consortium et al , 2013; Nikpay et al , 2015) consortium allowed the analysis of up to 180,000 individuals, about half of which had CAD.…”
Section: Genome‐wide Association Studies In Coronary Artery Disease Amentioning
confidence: 99%
“…H9C2 cells were cultured in DMEM supplemented with 15% fetal bovine serum and transfected with siRNA using Lipofectamine 2000 according to the manufacturer's instructions (Invitrogen). After 48 h of transfection, cells were harvested for assaying siRNA knockdown efficiency using quantitative real-time RT-PCR and Western blotting analysis as described (4,(22)(23)(24)(25). Sequences of primers used for quantitative real-time PCR analysis are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…3 Even after large-scale genome-wide association studies (GWAS) in European populations, GWAS in Asian populations have identified novel loci. [4][5][6][7] More additional loci are certainly left unidentified, and in such a situation, it remains elusive in total how many susceptibility loci exist. Here, to potently identify as many susceptibility loci as possible, GWAS and replication studies in a total of 44 673 Japanese participants were performed.…”
Section: Introductionmentioning
confidence: 99%